Simulation of the co-combustion of loaded activated charcoal in the combustion chamber of a waste incineration plant. (29th August 2007) - Vockrodt, Stefan; Leithner, Reinhard; Muller, Frank-Michael; Hopf, Norbert
Activated charcoal filters are widely used as the final stage of flue gas purification behind waste incineration plants. The used activated charcoal, loaded with sulphuric and nitric oxides, metals, mercury, dioxines, furanes and other pollutants, shall be burned in the combustion chamber of the plant. In order to achieve a stable ignition and a complete burnout of the charcoal, a newly developed oxygen-nitrogen solid fuel burner is used. The pulverized charcoal is fed by pneumatic transport with technical pure nitrogen as feed gas into the burner. Technical pure oxygen is added as oxidizing gas through coaxial channels and swirler blades. To predict both the efficiency of the burner and the influence on the flow field, emission and fouling behaviour of the combustor, simulations were carried out using the three-dimensional CFD code FLOREAN. Despite the small thermal capacity of the burner compared to the thermal capacity of the burned waste significant changes occur in the flow and temperature distribution inside the combustion chamber. Besides a slight rise of NOx emissions, the high local temperature peaks obtained can cause additional fouling and slagging of the furnace walls.